1999
DOI: 10.1111/j.1558-5646.1999.tb05388.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Geographic Variation in Rejection Behavior of Cuckoo Eggs by European Magpie Populations: An Experimental Test of Rejecter-Gene Flow

Abstract: Host responses toward brood parasitism have been shown to differ among populations depending on the duration of sympatry between host and parasite, although populations not currently parasitized show rejection behavior against parasitic eggs. The persistence of rejection behavior in unparasitized host populations and rapid increases of rejection rate in parasitized ones have sometimes been explained as the result of gene flow of rejecter genes from sympatry to allopatry (rejecter-gene flow hypothesis). We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
125
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 54 publications
(64 reference statements)
2
125
0
Order By: Relevance
“…However, Møller and Soler (2012) recently reviewed the literature on consistency in host responses to brood parasites and found large intraspecific variation in resistance in several host species (Cruz and Wiley 1989;Nakamura 1990;Soler 1990;Soler and Møller 1990;Briskie et al 1992;Lindholm 1999;Soler, Martínez, et al 1999;Moskát et al 2002;Martín-Gálvez et al 2006Moskát et al 2008;Stokke et al 2008;Avilés et al 2011;Soler et al 2011;Langmore et al 2012). These studies indicate that speciesspecific consistency in resistance is far from the rule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Møller and Soler (2012) recently reviewed the literature on consistency in host responses to brood parasites and found large intraspecific variation in resistance in several host species (Cruz and Wiley 1989;Nakamura 1990;Soler 1990;Soler and Møller 1990;Briskie et al 1992;Lindholm 1999;Soler, Martínez, et al 1999;Moskát et al 2002;Martín-Gálvez et al 2006Moskát et al 2008;Stokke et al 2008;Avilés et al 2011;Soler et al 2011;Langmore et al 2012). These studies indicate that speciesspecific consistency in resistance is far from the rule.…”
Section: Introductionmentioning
confidence: 99%
“…Soler, Martínez, et al (1999, 2001 showed for magpie Pica pica hosts that allopatric populations retained significant levels of resistance to cuckoos with this level depending on distance from areas of sympatry. The data that we have analyzed here do not allow for discrimination between the 2 hypothetical mechanisms (see also Thorogood and Davies 2013).…”
Section: Aq8mentioning
confidence: 99%
See 1 more Smart Citation
“…We used both kinds of eggs because the rejection rate of non-mimetic model eggs has a strong genetic component, whereas the main component of the rejection rate of mimetic model eggs is geographical distance rather than genetic distance (Soler et al 1999b). Thus, while di¡erences in the rejection rate of non-mimetic model eggs provide information on genetic di¡erences between populations of magpies, di¡erences in the rejection rate of mimetic model eggs provide information on the adult migration rates between populations (Soler et al 1999b).…”
Section: (B) Sampling and Study Areasmentioning
confidence: 99%
“…We used both kinds of eggs because the rejection rate of non-mimetic model eggs has a strong genetic component, whereas the main component of the rejection rate of mimetic model eggs is geographical distance rather than genetic distance (Soler et al 1999b). Thus, while di¡erences in the rejection rate of non-mimetic model eggs provide information on genetic di¡erences between populations of magpies, di¡erences in the rejection rate of mimetic model eggs provide information on the adult migration rates between populations (Soler et al 1999b). In other words, the rejection rates of non-mimetic model eggs could be used as an index of genetic di¡erences between populations in relation to the ability of magpies to recognize dissimilar eggs in their nests, but it could not be directly related to the current impact of brood parasitism on host populations because the rejection rates of non-mimetic model eggs will probably be related to gene £ow due to recognizer individuals from areas of sympatry or allopatry with the great spotted cuckoo (Soler et al 1999b).…”
Section: (B) Sampling and Study Areasmentioning
confidence: 99%